Relationship between newborn mid-upper-arm circumference and birth weight - Muhammad Anwar Taufiq; Djauriah A. Madjid; J. S. Lisal; Dasril Daud (Paediatrica Indonesiana, 2009)
Background  Recording  an  accurate  birth  weight  by  primaryhealth care workers has been a problem in rural areas, leadingto a search  for  an alternative, inexpensive, age independent andnoninvasive method to predict neonatal well being. Mid-upper-armcircumference (MUAC) might be  an  alternative anthropometricmeasurement useful  to  estimate the state of nutrition.Objective  To  evaluate  the  relationship  between  MUAC  andbirth weight  in  low birth weight (LBW) and normal birth weight(NBW) infants.Methods  We  measured birth weight and  MUAC  of  newbornbabies  of  various gestational ages  at  Siti Fatimah Maternity  andChildren's Hospital  and  Dr.  Wahidin Sudirohusodo  GeneralHospital, Makassar,  South  Sulawesi, Indonesia.  Correlationtests and diagnostic accuracy using different cut-off points wereperformedResults There were 892 live birth newborns (117 LBW and  775NBW) included in the study.  The  sensitivity, specificity, positivepredictive value, and negative value  for  MUACs  of<  10.3  em  were94.9  %,  99.9%, 99.1%, and 99.2%, respectively.  The  sensitivity,specificity, positive predictive value, and negative value  for  MUAC< 10.4  em  were 99.1  %,  99.6%, 97.5%, and 99.9%, respectively.The  sensitivity, specificity, positive predictive value, and negativevalue for MUAC < 10.5  em  were 100%,99.4%, 95.9%, and 100%,respectively.Conclusion  There  is  a strong correlation between  MUAC  andbirth weight. Birth weight can be predicted with the followingequation: Birth weight= -1776.383  +  (416.95 newborn  MUACvalue).  The  optimal cut-off point  for  the newborn MUAC value  forLBW infants  is<  10.5 em.